2021
DOI: 10.1111/ahg.12425
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia‐mental retardation syndrome: Molecular genetics of a rare neuro‐dermal disorder

Abstract: Alopecia‐mental retardation syndrome (APMR) is a rare autosomal recessive neuro‐dermal disorder. It is characterized by heterogeneous phenotypic features, that is, absence of hair on the scalp, eyelashes, and eyebrows and mild to severe intellectual disability. So far, approximately 14 families (i.e., Iranian, Pakistani, and Swiss) with APMR have been reported in the scientific literature. Its precise prevalence is still unknown, but according to a predictive estimate, it prevails with the ratio of 1 in 1,000,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…The cardinal signs of the syndromes are loss of scalp hair and eyelashes as well as intellectual disability (ID). APMR are four types classified based on the degree of ID, as well as associated clinical manifestations (Muzammal et al 2021 ). Clinical heterogeneity was observed among types of APMR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cardinal signs of the syndromes are loss of scalp hair and eyelashes as well as intellectual disability (ID). APMR are four types classified based on the degree of ID, as well as associated clinical manifestations (Muzammal et al 2021 ). Clinical heterogeneity was observed among types of APMR.…”
Section: Introductionmentioning
confidence: 99%
“…However, alopecia intellectual disability syndromes 4 (APMR4) (OMIM# 618,840) has a wider degree of affection when describing ID ranging from mild to severe (Besnard et al 2019 ; Sailani Reza et al 2017 ). APMR disorder predictive estimated prevalence is < 1:1,000,000 worldwide (Muzammal et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mutations located at the C-terminus of LSS are more likely to cause cataract, whereas the mutations located at the N-terminus of LSS tends to cause hair loss. In addition, mutations of LSS can cause alopecia-mental retardation syndrome (APMR), which is a rare autosomal recessive neuro-dermal disorder ( Muzammal et al, 2021 ). Thus, the studies on LSS mutations suggested that dysfunctions of LSS are far more complex and lead to autosomal-recessive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…1 APMR is classified into four subtypes based on the degree of intellectual disability and the associated clinical manifestations. 1 Alopecia-intellectual disability syndrome type 4 (APMR4, OMIM #618840) is a very rare, neuro-ectodermal syndrome caused by biallelic variants in LSS located on chromosome 21q22. 2 Lanosterol synthase (LSS) is an enzyme involved in the biosynthesis of cholesterol, steroid hormones, and vitamin D. 3 It catalyzes the rate-limiting step in the conversion of (S)-2,3-oxidosqualene into lanosterol.…”
Section: Introductionmentioning
confidence: 99%